Scientific production of Nursing on bone fractures in elderly people: an integrative review (Research, Society and Development, 2020)
Objective: To know the scientific production of nursing about bone fractures in elderly people. Methodology: This is an integrative literature review. Data collection was carried out in June 2019, in seven databases. Results: After applying the inclusion and exclusion criteria, ten studies in full remained for analysis, carried out in Brazil, Spain, United States of America, Sweden and Turkey. Three categories emerged: “Profile of elderly people who suffered bone fractures”; “Post-bone fracture processes in the elderly”; and “Nurse's role in assisting the elderly with bone fracture”. Final Considerations: This study made it possible to get to know the scientific production of nursing about bone fractures in the elderly. It was found that the publications of nurses addressing this theme is quite scarce and with a low level of evidence, however, the approach of it by nurses, takes place in a very particular, diverse and constructive way, which confirms that it is a wide area to be explored, disseminated and encouraged in the academic and professional field of Nursing.